Weldable fibre Bragg grating sensors for steel bridge monitoring - Barbosa, C. (2008)
For applications related to the structural health monitoring of steel bridges, novel weldable strain and temperature sensors based on fibre Bragg gratings were developed. These sensors, which can be directly welded to metallic structures, reveal linear responses over typical required measurement ranges and stability over thousands of load and temperature cycles. Proper installation procedures and in-field mechanical protection were also developed and implemented. The significance of the developed sensors was demonstrated through the installation of a complete sensing network on a new circular pedestrian bridge in Aveiro, Portugal, where it was used for loading tests, and also for in-service monitoring of its structural health.